ORAL CANDIDIASIS AMONG HIV PATIENTS ATTENDING AMINU KANO TEACHING HOSPITAL (FUDMA JOURNAL OF SCIENCES, 2023)
Candidiasis as an opportunistic infection that comes up in many different forms, depending on the part of the body involved and the category of patients affected. Oral candidiasis affects the oral cavity, and is a common phenomenon among HIV patients who are subject to immune depression. This study was to determine the burden of oral candidiasis among HIV patients in the study area. Samples were collected using sterile cotton tipped swabs and processed immediately. In the process, direct gram staining technique and KOH mount was carried out prior to culturing on Sabouraud dextrose agar followed by sub-culturing on chromogenic agar, to help in the phenotypic speciation of the different candida isolates after germ tube test was carried out. A total of 109 Candida species were isolated in this study, that include Candida albicans 72(66.1%), Candida glabrata 13(11.9%) and Candida krusie 24(22.0%). It was also discovered that age limit of 21-30 had the highest infection rate 32(29.4%) while the age range of 1-10 had the least 2(1.8%). Gender wise distribution indicated that 68(62.4%) of the 109 positive cultures were from females while 41(37.6%) were of males origin. In conclusion, results have revealed how Candida species are in close association with HIV infected individual which is of course a course for public health concern
Keywords: Oral Candidiasis, HIV patients, Opportunistic infections, Candida species